Synthesis and Molecular Docking Studies of New Dispiropyrrolidines on West Nile Virus NS2B-NS3 Protease - Nadia Mohamed Yusoff; Hasnah Osman; Mohd. Zaheen Hassan; Mohamed Ashraf Ali; Yeong Keng Yoon; Ezatul Ezleen Kamarulzaman; Muhammad Solehin Abd Ghani; Unang Supratman; Mohamad Nurul Azmi Mohamad Taib (Indonesian Journal of Chemistry, 2021)
West Nile virus (WNV) is among the other four flavivirus genus, rapidly spreading worldwide. The number of cases increases globally as there are no clinically available approved drugs and vaccines against this disease. Based on our previous finding related to a flavivirus, a series of spiropyrrolidine derivatives were regioselectively synthesized via [3+2]-cycloaddition reaction of three components between isatins, sarcosine, and (E)-3,5-bis (arylidene)-4-piperidones. The yield of synthesized compounds was in a range between 81–95%. The structures of all the synthesized compounds were characterized using FT-IR, 1D- and 2D-NMR, and HRMS. Molecular docking studies of spiropyrrolidines on NS2B-NS3 protease were done to understand and explore the ligand-receptor interactions and hypothesize the drug's refinements. The inhibition of NS2B-NS3 protease has been considered a promising strategy because this enzyme is responsible for the viral replication process. Among them, compound 5c shows an excellent binding affinity with ‒7.71 kcal/mol free binding energy and an inhibition constant of 1.73 μM. It also showed the binding orientation into the active site of WNV NS2B-NS3 protease on Asn84, Tyr1161, Gly1151, and Gly1153.